Comparison of transversus abdominis plane block versus local anesthetic wound infiltration for postoperative analgesia in lower abdominal surgery - Shakya, S; Rana, RB; Shakya, A (Devdaha Medical Journal, 2026)
Introduction: Postoperative pain control following laparotomy is vital for faster recovery, reduced opioid use and better patient comfort. The Transversus Abdominis Plane (TAP) block, which anesthetizes T6–L1 nerves between the internal oblique and transversus abdominis muscles, provides more consistent and longer-lasting analgesia of the anterior abdominal wall than Local Anesthetic Wound Infiltration (LAWI). Although LAWI is simple and widely available, its analgesic effect is less reliable, making the TAP block a more effective option in multimodal pain management. :To compare Postoperative pain scores,Opioid consumption, analgesia duration and incidence of postoperative nausea andvomiting(PONV)between TAP and LAWI groups following laparotomy. Methods: This double-blinded comparative study was conducted at Nepalgunj Medical College, Nepal (Aug–Dec 2024) after ethical approval. Adults aged 18–65years with ASA physical status I or II undergoing elective or emergency lower-abdominal surgery under general anesthesia were randomized (N=62) into two equal groups using sealed envelopes. Group A received LAWI with 20mL 0.25% bupivacaine before closure, while Group B received an ultrasound-guided bilateral TAP block with 10mL 0.25% bupivacaine on each side. Postoperative pain (Visual Analogue Scale, 0–10) was assessed at 0, 4, 8, 12, and 24 hours by a blinded investigator. Rescue analgesia (tramadol 50mg IV) was given for VAS > 4. Total 24-hour tramadol use and adverse events were recorded. Data were analyzed using chi-square, unpaired t-test and Mann–Whitney U-test; p < 0.05 was significant. Results: Both groups were comparable in age, gender, physical status and surgery duration. TAP block patients had statistically significant lower VAS scores at all time points. The mean time for first rescue analgesia was 348.39 ± 121.40 minutes in Group A while 461.54 ± 66.56 minutes in Group B(p<0.001). Total 24-hr tramadol requirement was higher in Group A (82.26 ± 35.47mg) than Group B (50 ± 00mg)(p<0.001). Eight patients in Group A and five in Group B developed postoperative nausea (PONV) with no significant difference (p>0.05). Conclusion: Ultrasound-guided TAP block with 0.25% bupivacaine is safe and highly effective for postoperative abdominal surgery analgesia, offering longer pain relief, reduced analgesic use and fewer side effects.